PENGARUH MODAL SENDIRI TERHADAP SISA HASIL USAHA PADA KPRI RUKUN BANJARHARJO KABUPATEN BREBES - Sri Rahayu; Siti Hafidoh (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2018)
This study aims to determine the effect of own capital on the remaining business results and the magnitude of the influence of own capital on the remaining business results in KPRI Rukun Banjarharjo Brebes Regency. The analytical tool used is the t test and simple correlation regression analysis. With the help of the SPSS Ver.16 program, the results show that based on the significance test with the degree of freedom (9-2) and 95 percent confidence level (ᾶ = 0.05), tcount is 14.487, which is greater than the t table of 1.89458, which means that there is a significant relationship between own capital to the remaining business results and the results of regression calculations obtained regression equation: = 27,580,594,795+ 0.013 x, which means that the capital itself has a positive effect on the remaining operating results. From the results of the calculation of the correlation coefficients obtained the results of 0.839, which means that the relationship of capital itself with the remaining business results is very large because the correlation coefficient is close to 1.